Minor histological components predict the recurrence of patients with resected stage I acinar- or papillary-predominant lung adenocarcinoma - Liu, Wei; Zhang, Qian; Zhang, Tiantian; Li, Li; Xu, Chunhua (Frontiers in Oncology, 2022)
Objective: Invasive lung adenocarcinoma is composed of five different histological subgroups with diverse biological behavior and heterogeneous morphology, the acinar/papillary-predominant lung adenocarcinomas are the most common subgroups and recognized as an intermediate-grade group. In the real world, clinicians primarily consider predominant patterns and ignore the impact of minor components in the prognosis of lung adenocarcinoma. The study evaluated the clinicopathologic characteristics of the lepidic, solid, and micropapillary patterns as non-predominant components and whether the minimal patterns had prognostic value on acinar/papillary-predominant lung adenocarcinomas. Methods: A total of 153 acinar/papillary-predominant lung adenocarcinoma patients with tumor size ≤4 cm were classified into four risk subgroups based on the presence of lepidic and micropapillary /solid components: MP/S−Lep+, MP/S+Lep+, MP/S−Lep−, and MP/S+Lep− groups. The Cox-proportional hazard regression model was used to assess disease-free survival (DFS). Results: The risk subgroups based on the non-predominant patterns were associated with differentiation (P = 0.001), lymphovascular invasion (P = 0.001), and recurrence (P = 0.003). In univariate analysis, DFS was correlated with non-predominant components (P = 0.014), lymphovascular invasion (P = 0.001), CEA (P = 0.001), and platelet-to-lymphocyte ratio (PLR) (P = 0.012). In the multivariate analysis, non-predominant components(P = 0.043) and PLR(P = 0.032) were independent prognostic factors for DFS. The 5-year survival rates of MP/S−Lep+, MP/S+Lep+, MP/S−Lep− and MP/S+Lep− subgroups were 93.1%,92.9%,73.1%,61.9%, respectively. The MP/S−Lep+ subgroup had the favorable prognosis than MP/S+Lep− subgroup with a statistically significant difference (P = 0.002). As minor components, the lepidic patterns were a protective factor, and the solid and micropapillary components were poor factors. The recurrence was related to the presence of non-predominant patterns rather than their proportion. Adjuvant chemotherapy did not significantly improve the prognosis of the MP/S+Lep- subgroup(P = 0.839). Conclusions: Regardless of the proportion, the presence of micropapillary/solid components and the absence of lepidic patterns are aggressive factors of DFS in patients with resected stage I acinar- or papillary-predominant lung adenocarcinoma.